Economics of the family - Browning, Martin; Chiappori, Pierre-André; Weiss, Yoram (Cambridge : Cambridge University Press, 2014)
The family is a complex decision unit in which partners with potentially different objectives make consumption, work and fertility decisions. Couples marry and divorce partly based on their ability to coordinate these activities, which in turn depends on how well they are matched. This book provides a comprehensive, modern and self-contained account of the research in the growing area of family economics. The first half of the book develops several alternative models of family decision making. Particular attention is paid to the collective model and its testable implications. The second half discusses household formation and dissolution and who marries whom. Matching models with and without frictions are analyzed and the important role of within-family transfers is explained. The implications for marriage, divorce and fertility are discussed. The book is intended for graduate students in economics and for researchers in other fields interested in the economic approach to the family.
Machine generated contents note: Introduction; Part I. Models of Household Behavior: 1. Facts; 2. The gains from marriage; 3. Preferences and decision making; 4. The collective model: a formal analysis; 5. Empirical issues for the collective model; 6. Uncertainty and dynamics in the collective model; Part II. Equilibrium Models of the Marriage Market: 7. Matching on the marriage market: theory; 8. Sharing the gains from marriage; 9. Investment in schooling and the marriage market; 10. An equilibrium model of marriage, fertility, and divorce; 11. Children and family structure.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Families -- Economic aspects; Households -- Economic aspects